Structural variation and rates of genome evolution in the grass family seen through comparison of sequences of genomes greatly differing in size. (17th June 2018) - Dvorak, Jan; Wang, Le; Zhu, Tingting; Jorgensen, Chad M.; Deal, Karin R.; Dai, Xiongtao; Dawson, Matthew W.; Müller, Hans‐Georg; Luo, Ming‐Cheng; Ramasamy, Ramesh K.; Dehghani, Hamid; Gu, Yong Q.; et al.
Summary: Homology was searched with genes annotated in the Aegilops tauschii pseudomolecules against genes annotated in the pseudomolecules of tetraploid wild emmer wheat, Brachypodium distachyon, sorghum and rice. Similar searches were performed with genes annotated in the rice pseudomolecules. Matrices of collinear genes and rearrangements in their order were constructed. Optical BioNano genome maps were constructed and used to validate rearrangements unique to the wild emmer and Ae . tauschii genomes. Most common rearrangements were short paracentric inversions and short intrachromosomal translocations. Intrachromosomal translocations outnumbered segmental intrachromosomal duplications. The densities of paracentric inversion lengths were approximated by exponential distributions in all six genomes. Densities of collinear genes along the Ae . tauschii chromosomes were highly correlated with meiotic recombination rates but those of rearrangements were not, suggesting different causes of the erosion of gene collinearity and evolution of major chromosome rearrangements. Frequent rearrangements sharing breakpoints suggested that chromosomes have been rearranged recurrently at some sites. The distal 4 Mb of the short arms of rice chromosomes Os11 and Os12 and corresponding regions in the sorghum, B . distachyon and Triticeae genomes contain clusters of interstitial translocations including from 1 to 7 collinear genes. The rates of acquisition of major rearrangements were greater in the large wild emmer wheat and Ae . tauschii genomes than in the lineage preceding their divergence or in the B . distachyon, rice and sorghum lineages. It is suggested that synergy between large quantities of dynamic transposable elements and annual growth habit have been the primary causes of the fast evolution of the Triticeae genomes. Significance Statement: Extensive literature exists on evolution of plant genes but less is known about evolution of plant genomes and their rate of change. Our study compared sequences of six grass genomes, identified colinear genes and rearrangements in their order, and showed that the rates of acquisition of major chromosome rearrangements has been greatly accelerated in the large genomes of annual Triticeae species.